Historiography of the Holy Alliance - Aleksandr Il'iashenko (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
The article analyses the evolution of domestic and foreign researchers' ideas about the essence of the Holy Alliance. The periodisation of historiography is proposed, based on the allocation of significant stages in the evolution of problems, source base, methodology and concepts of researchers. At the first stage in the XIX century domestic historians consider the activity of Alexander I from apologetic positions The article analyses the evolution of domestic and foreign researchers' ideas about the essence of the Holy Alliance. The periodisation of historiography is offered, based on the allocation of significant stages in the process of evolution of problems, source base, methodology and concepts of researchers. In the centre of attention of historians is the activity and views of Emperor Alexander I, his religious and mystical constructions and projects of peaceful arrangement of Europe after Napoleon's defeat. Researchers differ in their assessments of the tsar's independence in the international arena, in the degree of involvement of his entourage in the process of formulating the ideas of the Holy Alliance, as well as in questions of the goals and essential content of the Alliance, which was part of the pan-European system. The most significant way of interaction between the European powers during the period of the Holy Alliance is its congresses. The development of historiography begins with the domestic studies of the XIX century, in which Alexander I is considered from apologetic positions. During this period, the collection and publication of sources begins. The process of accumulation of the source base continues in the early twentieth century, when a critical attitude to the tsar's actions prevails in historiography. The Soviet period is characterised by stagnation in the study of the Holy Alliance, turning to socio-economic issues. At this time, foreign historiography is actively developing, in which a number of significant concepts and approaches emerge, explaining the essence and significance of the Holy Alliance. At the present stage, the range of problems considered by domestic and foreign researchers is increasing, the number of approaches and concepts is expanding, secondary sources are being studied and documents introduced earlier are being reinterpreted.